SOCIAL MEDIA AS AN AUTONOMOUS LEARNING FACILITY TO ENHANCE WRITING SKILL IN DIGITAL ERA - Sari, Retma (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This paper focuses on the using of social media as part of digital medias to enhance writing skill that to be one of  issues of Indonesian students. Internet facilities and social media are becoming increasingly important and take a strategic role in most of human activities included education and learning sector. The study was conducted at Tidar University, explored the experiences of second semester students supported the hypothesis that as students from non-English countries enter the globalization era where English is the norm, they are faced with the challenge of learning a new language especially in writing which has many requirements to make it such as vocabularies, grammar ideas and habit as a prerequisite to successful and further thriving .The fact that Indonesian students often played digital media as online communication stimulates young learners social connectedness. Academic achievement would also benefit from their activities, having access to a teaching material aimed at delivering skills for the use of Internet and digital technology. From the qualitative research done, the writer explored the new trend of digital media especially using social media to enhance writing ability as the facilities in autonomous learning because they are confronted with social media in their daily life anyway where they could use many channels they wanted to receive the information and learnt to share their writing freely and comfortably. From  findings, it can be concluded that social media boosts the writing proficiency, influences the autonomy and promotes independent of learning writing, improves the vocabularies references, increases the confidences, explores the experience and styles  also solves other academic difficulties such as grammatical rules, exploring  and also developing ideas